An interpretable machine learning model for predicting myocardial injury in patients with high cervical spinal cord injury - Li, Jiaqi; Zhang, Bingyu; Liao, Ye; Wei, Liqin; Huang, Qinfeng; Lin, Lijun; Chen, Jiaxin; Chen, Hui (Frontiers in Genetics, 2025)
BackgroundHigh cervical spinal cord injury (HCSCI) is associated with severe autonomic dysfunction and an increased risk of cardiovascular complications, including myocardial injury. However, early identification of myocardial injury remains challenging because of the lack of predictive tools.MethodsA total of 454 patients with HCSCI were retrospectively enrolled and categorized into myocardial injury (n = 101) and non-injury (n = 353) groups. Univariate and multivariate logistic regression analyses were used to identify independent risk factors. Four machine learning (ML) models—logistic regression, gradient boosting machine (GBM), neural network (NeuralNetwork), and adaptive boosting (AdaBoost)—were constructed to predict myocardial injury, and model performance was evaluated using the area under the curve (AUC), F1 score, and average precision (AP). SHapley Additive exPlanations (SHAP) was applied for model interpretability.ResultsMultivariate analysis identified dyspnea [odds ratio (OR) = 3.32; 95% confidence interval (CI): 1.49–7.39] and low hematocrit (OR = 2.18; 95% CI: 1.04–4.57) as independent predictors of myocardial injury. Among the ML models, the neural network model achieved the highest AUC and F1 score in the testing set and demonstrated superior calibration and net clinical benefit. The SHAP analysis revealed that dyspnea, low-density lipoprotein (LDL), spinal cord segment level, paralysis status, hematocrit, and myocardial injury stage were the top predictors. Individualized SHAP force plots illustrated the contribution of each feature to prediction outcomes.ConclusionWe developed an interpretable ML model capable of accurately predicting myocardial injury in patients with HCSCI. The neural network model showed the best overall performance and, with SHAP interpretation, provided transparent and individualized risk insights, supporting early diagnosis and targeted management in clinical practice.